Macrobrachium chainatense sp. nov. (Decapoda: Palaemonidae): a freshwater prawn from Thailand based on morphology and molecular phylogeny - Saengphan, Nukul; Panijpan, Bhinyo; Senapin, Saengchan; Laosinchai, Parames; Ruenwongsa, Pintip; Suksomnit, Auaree; Phiwsaiya, Kornsunee (Zootaxa, 2019)
Many species of freshwater prawns, large and small, inhabit Southeast Asian countries. In Thailand alone, there have been recent reports of new species in the genus Macrobrachium. Morphological differentiation and, recently, DNA sequence differences have been used to distinguish new species from valid ones. Macrobrachium chainatense (Decapoda: Palaemonidae), a small freshwater prawn found in Thailand, is now established as a new species based on both morphological and genetic criteria. Among Thailand Macrobrachium prawns, M. chainatense has smallest body size, largest egg size, and 3–5 teeth on the cutting edges. The most closely related Macrobrachium species to M. chainatense in terms of COI and 18S DNA sequences is M. niphanae. Their COI sequences differ by 7.3% while their 18S sequences are basically identical in all but one site. Observations of some aspects of this prawn in captivity are also utilized to establish its unique species status. This prawn may be useful as a source of cooked food for human consumption.